NETosis as an oncologic therapeutic target: a mini review - Jaboury, Sarah; Wang, Kenny; O’Sullivan, Kim Maree; Ooi, Joshua Daniel; Ho, Gwo Yaw (Frontiers in Immunology, 2023)
Neutrophil Extracellular Traps (NETs) are a key form of pro-inflammatory cell death of neutrophils characterized by the extrusion of extracellular webs of DNA containing bactericidal killing enzymes. NETosis is heavily implicated as a key driver of host damage in autoimmune diseases where injurious release of proinflammatory enzymes damage surrounding tissue and releases 70 known autoantigens. Recent evidence shows that both neutrophils and NETosis have a role to play in carcinogenesis, both indirectly through triggering DNA damage through inflammation, and directly contributing to a pro-tumorigenic tumor microenvironment. In this mini-review, we summarize the current knowledge of the various mechanisms of interaction and influence between neutrophils, with particular attention to NETosis, and cancer cells. We will also highlight the potential avenues thus far explored where we can intercept these processes, with the aim of identifying promising prospective targets in cancer treatment to be explored in further studies.